Preventive Effects of Mallotus japonicus Cortex Extracts on Dextran Sulfate Sodium-Induced Ulcerative Colitis in C57 BL/6J Mice - Kimura, Yoshiyuki (Natural Products Journal, The, 2020)
Background: The cortex of Mallotus japonicus (Euphorbiaceae) has traditionally been used to treat gastric ulcers, duodenal ulcers, and gastric hyperacidity in Japan. A large number of studies have recently focused on its effects on Inflammatory Bowel Disease (IBD). Objective: The aim of the present study was to examine the effects of M. japonicus (MJ) extracts on large intestinal diarrhea and inflammation using Inflammatory Bowel Disease (IBD) mouse models. Methods: The present study used 3% Dextran Sulfate Sodium (DSS)-treated colitis models. Red blood cell, platelet, and leukocyte counts in addition to hematocrit (Ht), hemoglobin (Hb), and colonic cytokine and chemokine levels were measured in DSS-treated C57BL/6J mice during the experimental period. Results: The Disease Activity Index (DAI) was lower in 3% DSS-treated mice orally administered MJ (200 and 500 mg/kg) than in mice administered 3% DSS only. Furthermore, MJ inhibited decreases in red blood cell and platelet counts as well as Hb and Ht levels in DSS-treated mice. Colon histology using direct fast scarlet staining revealed that MJ prevented mucosal membrane ulceration and eosinophil infiltration of the mucosal membrane induced by the DSS treatment. Increases in colonic Monocyte Chemoattractant Protein 1 (MCP)-1, interleukin (IL)-1β, and Tumor Necrosis Factor (TNF)-α levels in DSS-treated mice were reduced by orally administered MJ extracts. Conclusion: The present results suggest that M. japonicus cortex extracts are an effective treatment for IBD through the inhibition of increases in colonic IL-1β, TNF-α, and MCP-1 levels and eosinophil infiltration of the colon in DSS-treated mice.
Keywords: monocyte chemoattractant protein 1